Broadening perspectives in interventional cardiology. The role of EAPCI in supporting interventional cardiologists - Erik Rafflenbeul; Mario Iannaccone; Aleksandra Gasecka; Nicola Ryan; Alaide Chieffo (REC: Interventional Cardiology (English Ed.))
INTRODUCTION The European Association of Percutaneous Cardiovascular Interventions (EAPCI) was founded back in 2006 from the former European Society of Cardiology (ESC) Working Group on Interventional Cardiology. Within the ESC, and as 1 of 7 different sub-specialties associations, EAPCI mission is specifically aimed at reducing the burden of cardiovascular disease through percutaneous cardiovascular interventions. EAPCI empowers interventional cardiologists through a robust network of resources specifically designed to meet the demands of contemporary practice. In the following sections, we will outline the key benefits of EAPCI membership across several domains, including science, content, education, advocacy, and collaboration (figure 1). Each of these pillars contributes to a framework that not only keeps members at the cutting edge of interventional cardiology, but also fosters collaboration with national working groups and societies to move the field forward collectively. Figure 1. Why join the European Association of Percutaneous Cardiovascular Interventions (EAPCI)? By highlighting these core advantages, we hope we can underscore the true value of EAPCI membership in helping interventional cardiologists navigate the current fast-paced clinical environment and drive the future of interventional cardiology to improve daily clinical practice and scientific projects. SCIENTIFIC ACTIVITIES CONDUCTED BY EAPCI EAPCI scientific documents provide guidance for the clinical management of topics not covered in...